INFLUENCE OF QUALITY OF EXTERNAL SURFACE TO CHANGE LIFT AIRCRAFT - V. G. Kiselevich; V. G. Tsipenko; N. I. Chekalova (Научный вестник МГТУ ГА)
The article examines influence of quality of external surface to change lift aircraft.